The challenges of Bacillus of Calmette-Guerin (BCG) therapy for high risk non muscle invasive bladder cancer treatment in older patients. Issue 5 (September 2018) - Racioppi, Marco; Di Gianfrancesco, Luca; Ragonese, Mauro; Palermo, Giuseppe; Sacco, Emilio; Bassi, PierFrancesco
Abstract: Objectives: To evaluate the efficacy and safety of a tailored endovesical immunotherapy protocol with biweekly BCG for elderly Patients with high risk non muscle invasive bladder cancer (HG-NMIBC). Materials and Methods: We retrospectively evaluated data from 200 patients older than 80 years newly diagnosed with HG-NMIBC: 100 (group 1) with multiple comorbidities (WHO PS 2–3, ASA score ≥3, Charlson Comorbidity index ≥3, GFR<60 mL/min) were treated with BCG induction course administered biweekly; 100 (group 2) with statistically significant better conditions were treated with standard weekly BCG therapy. After the induction treatment disease-free patients underwent to at least one year of BCG maintenance therapy. Endpoints were: initial response to BCG, cancer-free survival and rate of progression at 2 years, rate of complications. Results: No statistically significant differences were found in terms of initial response to BCG (69% in Group 1 vs 71% in Group 2, P = 0.75), cancer free survival (57% vs 55% respectively, P = 0.77) and rate of progression (20% vs 14% respectively, P = 0.26) at 2 years. The difference in the rate of overall complications was statistically significant (15% in Group 1 vs 27% in Group 2, P = 0.03), in the rate of severe complications was not statistically significant (5% in Group 1 vs 7% in Group 2, P = 0.61). Conclusion: A tailored regimen of BCG administration is possible and safe in frail elderly patients, limiting side effects and risk of undertreatment but maintaining oncological outcomes. Preliminary results in a small patients group are promising but larger randomized studies are needed to confirm our data.